EVOLUTION OF THE KOMANDORSKAYA BASIN - Shipilov E.V.; Yunov A.Yu. (My University, 1989)
The wedgelike shape of the Komandorskaya Basin in plan view, the distribution of thicknesses of the sedimentary mantle and its structure, the characteristic topography of the basement in the region, the crustal structure at depth and the anomalously high heat-flow values suggest that destructive processes dominated in the evolution of the crust in this area of the sea. The cyclical development of this zone of the sea fits the major transgressive and regressive Cenozoic cycles identified by Vail in the ocean. It is obvious in this case that Vail's eustatic cycles are closely connected with tectonic activation phases.
Keywords: Cenozoic; Cenozoic; Кайнозой